Vitamin D treatment improves levels of sexual hormones, metabolic parameters and erectile function in middle-aged vitamin D deficient men. (2nd January 2017) - Canguven, Onder; Talib, Raidh A.; El Ansari, Walid; Yassin, Dany-Jan; Al Naimi, Abdullah
Abstract: Background : The associations between serum vitamin D (VD), serum testosterone (TT) and metabolic syndrome are complex and with limited published research, particularly on the effects of VD treatment on sexual hormones, erectile function and the metabolic syndrome. Objectives : This study assessed whether a monthly high dose VD treatment for 12 months in VD deficient middle-aged men was associated with: changes in levels of sexual hormones, improvement of diabetes control and metabolic syndrome components, better erectile function [International Index of Erectile Function (IIEF)-5 questionnaire]; and changes in a prostate marker. Materials and methods : Descriptive research of a prospective study, conducted between October 2014 and September 2015, 102 male patients ≥35 [(±SD: 53.2 ± 10.5), (range 35–64)] years with deficient serum VD level (<30 ng/mL) were included in the study. Participants were followed up for one year, with monitoring at 3-, 6-, 9- and 12-months. At the initial baseline visit, a complete medical examination was conducted, and blood was drawn for laboratory tests for above biochemical and hormonal variables under examination. Participants received an initial VD (Ergocalciferol; oral solution 600 000 IU/1.5 ml), and followed a VD treatment regime thereafter. At the four follow up visits (3, 6, 9 and 12 months), blood was collected, and patients' erectile function was evaluated by IIEF-5 questionnaire. Main outcome measures : During the follow up visits, all the biochemical and hormonal (TT, estradiol and luteinizing hormones, HbA1c, serum lipids profile) were assessed, and patients' erectile function was evaluated by IIEF-5 questionnaire. Results : Patients' mean age was 53.2 ± 10.4 years. Serum VD exhibited significant increments ( p <0.001) from baseline (15.16 ± 4.64 ng/mL), to 3 (31.90 ± 15.99 ng/mL), 6 (37.23 ± 12.42 ng/mL), 9 (44.88 ± 14.49 ng/mL) and 12 months (48.54 ± 11.62 ng/mL), and there was significant stepladder increases in both serum TT level (12.46 ± 3.30 to 15.99 ± 1.84 nmol/L) and erectile function scores (13.88 ± 3.96 to 20.25 ± 3.24) ( p <0.001 for both). We also observed significant stepladder decreases in estradiol (87.90 ± 27.16 to 69.85 ± 14.80 pmol/L, p = 0.001), PTH (from 58.52 ± 28.99 to 38.33 ± 19.44 pg/mL, p <0.001) and HbA1c levels (7.41 ± 2.85 to 6.66 ± 1.67%, p = 0.001). Mean BMI significantly decreased from 33.91 ± 6.67 to 33.14 ± 6.35 kg/m 2 ( p = 0.001); and PSA values significantly increased from 0.59 ± 0.30 to 0.82 ± 0.39 ng/mL ( p <0.001) at the end of the 12 months' follow-up. There were no changes in LH levels. Conclusion : This study demonstrated that VD treatment improves testosterone levels, metabolic syndrome and erectile function in middle-aged men. More randomized placebo-controlled interventional trials of VD treatment in patients with the metabolic syndrome and low TT could assist in uncovering the putative roles of VD.